Constituents of the Rhizomes of Alpinia rafflesiana - Mohd Sirat, Hasnah (Universiti Putra Malaysia Press, 1996)
The chemical constituents of the rhizomes of Alpinia rafflesiana were studied and four components were isolated by chromatographic techniques and their structures identified by spectroscopic methods. The major constituent has been identified as chalcone flavokawin B, while the minor constituents have been assigned as methyl cinnamate, diarylheptanoid 1,7-diphenyl-5hydroxy- 6-hepten-3-one and 5,6-dehydrokawain.